Association between public health nurses' involvement in local healthcare planning and the corresponding off‐the‐job training. Issue 2 (12th September 2022) - Yoshioka‐Maeda, Kyoko; Shiomi, Misa; Katayama, Takafumi; Hosoya, Noriko; Fujii, Hitoshi; Mayama, Tatsushi
Abstract: Objective: This study investigated the association between receiving off‐the‐job training and the involvement of public health nurses in local healthcare planning. Design: A nationwide, cross‐sectional study design. Methods: We sent self‐report questionnaires to 2, 185 public health nurses with experience in developing local healthcare plans in Japan since 2013 and collected information related to three main categories: demographic data, involvement in local healthcare planning and strategies for healthcare planning. Results: We received 1, 281 responses (return rate of 58.6%), of which 231 did not meet the inclusion criteria. Thus, we analysed 1, 050 valid responses. Among the 1, 050 respondents, 496 (47.2%) had received off‐the‐job training in healthcare planning. A subsequent logistic regression analysis revealed that the following factors were associated with this achievement: holding a managerial position, receiving healthcare planning education at the undergraduate level, having mentors regarding the promotion of it, partially conducting cross‐sectional coordination and conducting groupwork with community‐dwelling residents.